Archaeology, Heritage, and Moral Terrains: Two Cases from the Mesa Verde Region - Steve Wolverton; Robert Melchior Figueroa; Porter Swentzell (Ethnobiology Letters, 2016)
Multiple cultural identities converge in Mesa Verde archaeology. Archaeologists have engaged research questions for the last half century, leading to cultural reconstructive summaries about how Pueblo people lived prior to migrating out of the Mesa Verde region. The importance of this narrative centers on the identity of the researcher as an archaeologist. An increasingly recognized narrative among archaeologists is that of Pueblo identity, in which contemporary Pueblo people claim Mesa Verde villages and landscapes as part of their heritage. Generally speaking, Pueblo people and archaeologists navigate separate moral terrains, which pose multiple obstacles for both archaeologists and Pueblo people pertaining to the past, present, and future of the Mesa Verde region. A conceptual framework from environmental philosophy opens a platform for reconciliation by providing a relational narrative that empowers Pueblo identity and recalibrates archaeology. This environmental justice lens is applied to two archaeological research narratives, one centering on chemical analysis of biomolecular artifact residues and the other on paleohydrology and Pueblo farming.